EMPLOYEE ATTITUDES TOWARD CHANGE IN PUBLIC SECTOR ORGANIZATION - Mega Asri Zona (Unib Press Universitas Bengkulu, 2020)
This research aim to examine four constructs that represent employee attitudes towards organizational change; readiness for change, commitment to change, openness to change and cynicism about organizational change. This research would help the public organization to overcome changes.. This research is a type of descriptive research that aims to describe the nature of something that is ongoing at the time the research is conducted and examine the cause of a particular symptom. The population in this study are employees of public sector organizations that are undergoing organizational changes in the Province of West Sumatra. The sampling technique in this study uses purposive sampling where the sampling technique is based on a certain criterion. In this case the criteria for sampling are employees with organizations that are undergoing changes. The data collection technique used was a survey by distributing questionnaires to employees of public sector organizations in West Sumatra. The number of respondents in this study were 100 respondents. The result shows that openness to change have the highest mean, followed by readiness to change, commitment to change and cynicism about organizational change. It means that employees in public organization in West Sumatra are willing to accommodate and accept change. Keywords: employee attitudes towards organizational change; readiness for change; commitment to change; openness to change; cynicism about organizational change